The effect of diet type and feeding rate on growth, morphological development and behaviour of larval and juvenile goldfish Carassius auratus (L.) - Paulet, Timothy Guy (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2004)
Intensive grow-out of goldfish, Carassius auratus (L.), larvae and juveniles in closed recirculating systems requires the control of environmental conditions and feeding. This study investigated the effect of different diets, environmental condition and feeding level on growth, development and survival of goldfish larvae and juveniles. Prey preference for Artemia nauplii or decapsulated Artemia cysts as well as agonistic behaviour was recorded. The micrometer device used to measure mouth-gape was shown to produce accurate measurements which could be used to estimate the maximal particle size that can be ingested by goldfish larvae of a particular age. Goldfish completed metamorphosis earlier with an increased feeding level of Artemia cysts and by making the cysts more accessible to the fish using up-welling water movement. Morphometric plasticity in goldfish larvae was exhibited within two weeks of growth and it may be possible to induce changes in morphology by manipulating diet and rearing environment. Fish that fed on moving prey items had a significantly larger mouth-gape than those that browsed cysts from the tank bottom or dry food items. The development of mouth-gape was not affected by the feeding level of cysts. Condition factor increased with an increase in the number of cysts fed per fish per day. Goldfish larvae and juveniles grew faster and had a higher survival when fed on decapsulated Artemia cysts than on instar I Artemia nauplii or a mixed live/dry diet of Artemia nauplii and dry food. Feeding at least 155 cysts per fish per day, in tanks with upwelling water movement, gave the best growth and survival and the smallest size variation. In addition, cysts remained available to the fish for longer periods, and were easier to prepare and feed. Goldfish larvae preferred decapsulated Artemia cysts to nauplii and rejected fewer prey items as they grew older. The frequency of agonistic behaviour increased as fish grew but no cannibalism was recorded for cyst-fed fish. This study showed that decapsulated Artemia cysts are a good alternative to Artemia nauplii as a diet for larval goldfish. Good growth and high survival was achieved for cyst-fed goldfish larvae and juveniles at 23 Â± 1.5Â°C and at an initial stocking density of 12 fish per litre. This research also contributes to an understanding of feeding behaviour and attempts to minimise under- or over-feeding of Artemia cysts in order to reduce grow-out costs due to the high value of the feed type.
Keywords: Goldfish -- Growth; Goldfish -- Nutrition; Goldfish -- Development; Goldfish -- Larvae